Intelligent Kid's System: Framework For Intelligent Kid's System - Halim, Fandi (Universiti Sains Malaysia, 2010)
Currently education has become more important and crucial which has resulted in many research studies being conducted to enhance the way of learning especially for the children. In enhancing the learning process, it is crucial to include the role of technology and to use a web-based application which has intelligent aspect in their tutoring system to make the system more flexible in responding and giving feedback to the children. Intelligent Kid's System is a web-based game application system that enable the children to play while learning and at the same time to enable their parents to monitor their performance. This system is multiplayer online adventure game where the children can play together and communicate with each other in the system. Intelligent Kid's System utilized the concept of adaptive system that enable the system to adjust its content to suit the children ability to master the skills provided in the respective room in the system.